Akinetopsia: a systematic review on visual motion blindness - Browne, Johanna L.; Krabbendam, Lydia; Blom, Jan Dirk (Frontiers in Neurology, 2025)
BackgroundAkinetopsia, or visual motion blindness, is a perceptual distortion characteristic of Alice in Wonderland syndrome in which people see moving objects as disjointed ‘jumps’ or ‘freeze frames.’ Despite its profound impact, the condition remains poorly understood beyond the established centrality of cortical area V5/MT in visual motion perception.MethodsWe carried out a systematic review of case descriptions on motion blindness, including those where additional symptoms were described.ResultsOur search yielded data on 25 clinical and 27 experimental cases, the latter induced by cortical stimulation. Of the clinical cases, 12% showed hemiakinetopsia, 50% continuous or progressive symptoms, and 52% a chronic course. Pathophysiologically, in right-handed individuals, the left area V5/MT was found to be particularly susceptible to acute interference, as evidenced by the experimental studies. In contrast to earlier studies, we found a greater prevalence of right-hemispheric afflictions in clinical cases, suggesting that the right area V5/MT plays a more dominant role in motion perception. Bilateral lesions to V5/MT most often coincided with global akinetopsia and chronicity, although we found that the severity of the condition also depends on surviving components of the visual motion network as a whole, and—in line with the dynamic parallellism theory—the speed of moving objects. Aetiologically, most cases were associated with structural neurological conditions such as stroke and neurodegenerative disease, and fewer with intoxications or paroxysmal neurological disorders such as epilepsy. Treatments were mostly successful when they were aimed at the underlying condition, while cases due to organic lesions tended to be therapy-resistant. Although individual reports confirm that akinetopsia may have detrimental effects on people’s lives, data were insufficient for a proper analysis of such experiential aspects.ConclusionPhenomenologically, pathophysiologically, and etiologically, akinetopsia is more heterogeneous than previously thought. We provide recommendations for clinical practice and further scientific research.